(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
The article presents the results of a study on the effectiveness of combined therapy with magnesium supplementation and phytoestrogens in women aged 45–55 years with climacteric syndrome (CS) undergoing maintenance hemodialysis (HD). It was demonstrated that this group of patients exhibited a pronounced deficiency of magnesium, calcium, and vitamin D3, along with a significant increase in parathyroid hormone levels and moderate hyperkalemia, which worsened after dialysis sessions. Standard therapy did not provide relief of CS symptoms or improve quality of life (QoL). The inclusion of a magnesium-containing preparation and a phytoestrogen in the treatment regimen for 90 days led to a significant increase in serum magnesium, calcium, and vitamin D3 levels, normalization of hormonal balance, reduction of parathyroid hormone, as well as a marked decrease in clinical manifestations of CS. These changes were accompanied by an improvement in QoL without adverse effects. The findings highlight the importance of correcting hypomagnesemia and the potential role of phytohormonal agents in the comprehensive management of women with CS undergoing HD.